The Effect of Transformational Leadership and Career Management on Organizational Commitment with Job Satisfaction as an Interverning Variable - Siregar, Aisyah Huwaida; Budi Winarso, Anjar Prihantoro (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to analyse the effect of transformational leadership, career management on organisational commitment with job satisfaction as an interverning variable. The population of the study is active civil servants in the BP2MI environment, totalling 884 people (data as of December 2023). Determination of the number of research samples using the Slovin formula due to the limited and reachable population of 275 people. The sampling method used non-probability sampling with purposive sampling technique. This study uses a Structural Equation Model (SEM) approach with a measurement model using the Smart PLS version 3.2.9 programme. The results showed that Transformational Leadership had no significant direct influence on Organisational Commitment at BP2MI. Transformational Leadership had a significant direct influence on employee Job Satisfaction at BP2MI. Career Management had a significant direct influence on employee Job Satisfaction at BP2MI. Job Satisfaction had a significant direct influence on Organisational Commitment of employees at BP2MI. Job Satisfaction can mediate the effect of Transformational Leadership on Organisational Commitment at BP2MI. Job Satisfaction can mediate the effect of Career Management on Organisational Commitment at BP2MI.